2019
DOI: 10.1016/j.geomorph.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of historical landscape change on the foreland of a receding polythermal glacier, Hørbyebreen, Svalbard

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 93 publications
(96 reference statements)
1
27
0
Order By: Relevance
“…Bennett et al 1996) of crevasse fill and hydrofracture origins (Fig. 4B), and glacial lineations (Karczewski 1989;Karczewski et al 1990;Gibas et al 2005;Rachlewicz 2009;Szuman & Kasprzak 2010;Evans et al 2012;Ewertowski et al 2019). The present study focuses on the complex esker system on the eastern part of the foreland, which is melting out of the glacier snout ( Fig.…”
Section: Fig 2 Locations Of Study Areas Boxes In (A) Show the Locamentioning
confidence: 93%
See 1 more Smart Citation
“…Bennett et al 1996) of crevasse fill and hydrofracture origins (Fig. 4B), and glacial lineations (Karczewski 1989;Karczewski et al 1990;Gibas et al 2005;Rachlewicz 2009;Szuman & Kasprzak 2010;Evans et al 2012;Ewertowski et al 2019). The present study focuses on the complex esker system on the eastern part of the foreland, which is melting out of the glacier snout ( Fig.…”
Section: Fig 2 Locations Of Study Areas Boxes In (A) Show the Locamentioning
confidence: 93%
“…Previous studies, using Ground Penetrating Radar (GPR), have identified the thermal transition between warm-based ice further up-glacier and cold-based ice beneath the snout (Małecki et al 2013). Looped medial moraines observed on aerial photographs from 1936 indicate that Hørbyebreen surged at some point before this date (Ewertowski et al 2019) and has since undergone sustained snout recession, which has accelerated since the 1990s and is likely related to increased summer temperatures (Małecki et al 2013).…”
Section: Hørbyebreenmentioning
confidence: 99%
“…The rapid exposure of land from Svalbard glaciers (over 20% of glacierized terrain decrease) activates sediment cascades through which exposed glacigenic sediments are transported and can then be stored in the form of solifluction slope covers, fluvial floodplains, lakes and within the coastal zone in the form of beaches, tidal flats or as marine sediments in the bottoms of fjords (e.g. Lønne & Lyså, 2005;Midgley et al, 2018;Ewertowski et al, 2019;Weckwerth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the preservation potential of freshly exposed glacial landforms can be very low, as proglacial terrains are one of the most dynamic parts of the glaciated landscapes (cf. [1][2][3][4]).…”
Section: Introductionmentioning
confidence: 99%
“…Location of the study area; red circle indicates the approximate location of the surveyed part of the Hørbyebreen foreland. Reprinted from Geomorphology, 325: 40-54, Ewertowski et al, "Quantification of historical landscape change", Copyright (2019), with permission from Elsevier[4].…”
mentioning
confidence: 99%